2011
DOI: 10.1111/j.1708-8208.2011.00336.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship among Schneiderian Membrane, Underwood's Septa, and the Maxillary Sinus Inferior Border

Abstract: It is suggested that Underwood's septa may be the reason for the thinness of the Schneiderian membrane. However, future studies among larger groups are necessary for confirming the finding by using well-designed clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 22 publications
5
64
1
2
Order By: Relevance
“…It has also been demonstrated that males had thicker membrane thickness (0.74 mm) when compared to females (0.34 mm) (Cakur et al. ). Additionally, Shanbhag et al.…”
Section: Discussionmentioning
confidence: 93%
“…It has also been demonstrated that males had thicker membrane thickness (0.74 mm) when compared to females (0.34 mm) (Cakur et al. ). Additionally, Shanbhag et al.…”
Section: Discussionmentioning
confidence: 93%
“…Finally, 38 studies were eventually excluded for not meeting the strict inclusion criteria, and 31 studies that reported SMT were considered for qualitative analysis (Table 1). 12,13,15‐18,23‐47 Those studies reporting range or unclear data were excluded for the quantitative analysis (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 19 studies 13,15,17,18,23‐37 fulfilled the inclusion criteria for quantitative assessment. Mean ± SE SMT was 1.17 ± 0.1 mm (95% confidence interval [CI] = 0.89 to 1.44).…”
Section: Resultsmentioning
confidence: 99%
“…The density of the block simulating maxillary cancellous bone was determined to be 0.32 g/cm 3 with reference to previous studies [1516]. For the cortical layer of the maxilla, epoxy sheets (Sawbones; Pacific Research Laboratories Inc., Vashon, WA, USA) filled with short fibers were constructed to a thickness of 1 mm, considering previous studies that showed cortical bone thickness (1.49±0.34 mm) and the inferior border thickness of the maxillary sinus (0.86±0.21 mm) [1718]. The dimensions of each block were 3 cm×3 cm×the designated height.…”
Section: Methodsmentioning
confidence: 99%